A efetividade da proteção da identidade de gênero e do nome da pessoa transexual: análise de constitucionalidade e de convencionalidade - Silva, Beatriz Pereira da (2016)
Brazilian law does not expressly regulate gender identity and changing name and gender of the transsexual documents. This work is subject to legal protection of the name of transgender people. The objective of the research is, based on the premise that transsexuality is not a disease, seek legal elements to justify the withdrawal of the lawsuit requirement for rectification of the name of the transsexual person. Currently, the transsexual person is required to propose action in rectifying civil registration seat (Articles 55 and following of Law 6015/73) in order to obtain judicial authorization to conduct the name change. Most of time the judge only defers the request when the person has undergone genital reassignment surgery. This work aims to demonstrate that such legal requirement violates the rights of transgender people provided for the Constitution and the Human Rights treaties ratified by Brazil, as well as propose the name change in the administrative field